Relationship between serum HBsAg level, HBV DNA level, and peripheral immune cells in patients with chronic hepatitis B virus infection - Mukherjee, Rathindra Mohan (Hepatic medicine: evidence and research, 2010)
The chronicity of hepatitis B virus (HBV) infection is attributed to inappropriate functioning of cell-mediated immunity. Besides the importance of measuring serum HBV DNA and HBV surface antigen (HBsAg) as markers of viral replication and exposure, respectively, studies regarding their influence on immune cell status in chronic HBV infection are still scarce. Because such studies of chronic HBV patients have not been reported for India, we attempted to evaluate the relationship between serum concentrations of HBsAg, HBV DNA, and percentage of immune cells in peripheral blood of Indian subjects with chronic HBV infection. Thirty-one HbsAg-positive subjects were evaluated for serum HBe antigen (HBeAg), anti-HBe, and alanine transferase status by standard enzyme-linked immunosorbent assay (ELISA) and biochemical procedures. Serum HBV DNA level was determined by real-time TaqMan® polymerase chain reaction assay. Serum HBsAg level was measured by a third-generation sandwich ELISA kit. Peripheral immune cell profiling was done by multifluorometric flow cytometry analysis, for which 21 healthy subjects were included as controls. The majority (93.5%) of the study subjects were HBeAg-negative and anti-HBeAg-positive. Mean viral load, HBsAg, and alanine transferase levels were 4.20 ± 1.96 log copies/mL, 5.98 ± 4.62 log IU/mL, and 74.5 ± 110 IU/mL, respectively. In comparison with controls, total T cell and cytotoxic T cell populations were significantly (P < 0.05) reduced in HBV-infected subjects, while the status of B cells, natural killer cells, T helper cells, and ratio of T helper to cytotoxic cells remained unaltered. Suppression of the peripheral cytotoxic T cell population in chronic HBeAg-negative chronic HBV infection is influenced by increased viral load. Serum HBsAg concentration appeared independent of serum HBV DNA level and immune cell status. Nonelevation of natural killer cell and T helper cell numbers in subjects harboring lower to moderate HBV loads is further indicative of noninduction of innate as well as a coordinated adaptive immune response favoring chronicity of the disease.